2004
DOI: 10.1289/ehp.6586
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk and parental pesticide application in children of Agricultural Health Study participants.

Abstract: Parental exposure to pesticides may contribute to childhood cancer risk. Through the Agricultural Health Study, a prospective study of pesticide applicators in Iowa and North Carolina, we examined childhood cancer risk and associations with parental pesticide application. Identifying information for 17,357 children of Iowa pesticide applicators was provided by parents via questionnaires (1993-1997) and matched against the Iowa Cancer Registry. Fifty incident childhood cancers were identified (1975-1998). Risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
127
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(131 citation statements)
references
References 42 publications
2
127
1
1
Order By: Relevance
“…IARC classifies DDVP as a possible human carcinogen based on the increased incidence of leukemia found in animal studies, while another study observed serious immune alterations associated with DDVP exposure [6,9]. Some epidemiologic investigations [9,15,16,23,24] have reported associations with lymphatic and hematopoietic cancers, but we see no evidence for an association here for lymphohematopoietic cancers as a group. Numbers of leukemia and NHL were too small for meaningful individual analyses.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…IARC classifies DDVP as a possible human carcinogen based on the increased incidence of leukemia found in animal studies, while another study observed serious immune alterations associated with DDVP exposure [6,9]. Some epidemiologic investigations [9,15,16,23,24] have reported associations with lymphatic and hematopoietic cancers, but we see no evidence for an association here for lymphohematopoietic cancers as a group. Numbers of leukemia and NHL were too small for meaningful individual analyses.…”
Section: Discussioncontrasting
confidence: 59%
“…Early case reports linked DDVP exposure with leukaemogenic consequences, including acute lymphoblastic leukemia, in children [14]. A case-control study of leukemia among men in Iowa and Minnesota [15] found a significant two-fold risk associated with DDVP use and Flower et al found that prenatal parental exposure to DDVP was associated with an increased risk of childhood cancer, (odds ratio (OR) = 2.06, 95 percent confidence interval (CI): 0.86, 4.90) [16]. Dichlorvos use has also been shown to increase prostate cancer risk in a California study of farm workers (OR= 1.35, 95 percent CI: 0.86, 4.90) [17] and in the Agricultural Health Study (AHS) of pesticide applicators in Iowa and North Carolina who have a family history of prostate cancer (OR= 1.92, 95 percent CI: 0.98, 3.75) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings that exposure to pesticides sprayed on farms or companies near the home may be associated with higher odds of ALL are consistent with other studies that have examined associations between residential proximity to agricultural pesticide applications and childhood leukemia and other childhood cancers 7, 25, 26, 27, 28. Notably, previous studies have used exposure assessment methods such as geographic information systems to map pesticide use near the homes,25 analysis of pesticide use registry data,26 measurement of pesticide residues in home dust samples,27 or assessment of parental report of living in an agricultural area with pesticide use 7.…”
Section: Discussionsupporting
confidence: 91%
“…Leukemias and lymphomas are the most common type of childhood cancer, followed by tumors of the nervous system. The etiology of 80% to 90% of childhood cancers is unknown (1, 21-23), but considerable evidence exists for maternal exposure to environmental chemicals as contributors to development of childhood leukemias and lymphomas (24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The two environmental in utero exposures that have definitively been linked with increased cancer in children and young adults are diethylstilbestrol and ionizing radiation (1).…”
Section: Discussionmentioning
confidence: 99%